The Electronic Integrated Credit Agreement & Liability Registration Process - Dinda Laras Hapsari; Ira Alia Maerani; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The implementation of the imposition of Mortgage Rights in a credit agreement aims to provide legal certainty and protection for all parties in utilizing land and objects related to land as credit guarantees in accordance with applicable legal regulations. In the current digital era, the Mortgage registration system has changed from conventional to electronic which is applied simultaneously without going through a transition period and adequate socialization, causing obstacles in the process. This study used a sociological juridical approach. The sociology of law approach was an approach that is used to look at legal aspects in social interactions in society, and served as a support to identify and clarify findings of non-legal materials for research purposes or legal writing. The juridical factor is based on the Regulation of the Minister of ATR/BPN Number 5 of 2020 concerning Electronically Integrated Mortgage Rights. The research problems were analyzed and solved by the Theory of the Work of Law, Agreement Theory, Theory of Islamic Justice. Based on the results of research and discussion: 1) Process of credit agreement with mortgage at a bank in the city of Tegal; 2) Electronic Integrated Mortgage registration process; 3) Constraints and solutions in Electronically Integrated Mortgage registration. The conclusion of this legal writing is that in the process of credit agreement with mortgage and the electronically integrated mortgage registration process in the city of Tegal, it is in accordance with the Minister of ATR/BPN Regulation Number 5 of 2020 concerning Electronically Integrated Mortgage Services, but there are several obstacles in One of the reasons for the HT-el registration process was the lack of socialization carried out by the organizers.